ANALISIS PRAKTIK SOSIOKULTURAL DALAM PEMBERITAAN KASUS KORUPSI PADA MEDIA METRO TV DAN NET MELALUI PERSPEKTIF ANALISIS WACANA KRITIS NORMAN FAIRCLOUGH - Nur Indah Sholikhati (Universitas Sarjanawiyata Tamansiswa, 2018)
The objectives of this study are to analyze how mass television represents the news about corruption news as well as why mass television creates the corruption news itself. the mass television were Metro TV and NET as the objects of this study. The approach was descriptive qualitative by using critical discourse analysis by Norman Fairclough. There are three steps of critical discourse analysis by Norman Fairclough, including description, interpretation, and explanation. Based on this study, there are three aspects of creating news at Metro TV and NET. The first aspect is situational aspect, news discourse is influenced by politic situation in the beginning 2017 by holding Governor selection in DKI Jakarta and the owners of mass television use their authority to support their choices of Governor. Moreover, there is agreement about Peraturan Presiden (Perpres) No. 87 in 2016 about Satuan Tugas Sapu Bersih Pungutan Liar by Joko Widodo at October 2016. The second aspect is institutional aspect, there is the rival among the owner of mass television, KPK, and institution of corruption. The third aspect is social aspect, including economic, politic, and social context that become enthustiasm by citizens to support the institution of corruption itself.